Challenges and Adjustments of Healthcare and Labor Policies in Greece during the COVID-19 era: A Critical Assessment of the Key Social Policy Responses - Tzagkarakis, Stylianos Ioannis; Melidis, Michail (European Scientific Journal, ESJ, 2022)
The welfare state in Greece even before the outbreak of the global pandemic experienced multiple challenges and problems mainly as a result of its chronic structural, administrative, and financial problems which were further deteriorated by austerity measures. The pandemic that followed the ten-year economic crisis led to a new multifaceted crisis, adding further pressure on the National Health System as well as on the labor market, and precipitating the uptake of targeted measures and policies to support both the NHS with equipment, staff, and employment due to the imposition of national and local lockdowns. Confronted with such weaknesses, the establishment of a new welfare state would need to bear a higher degree of flexibility, inclusivity, and efficiency in order to live up to the increasing societal, health, and economic demands. In this sense, the aim of this paper is to explore the variations in health and labor policies (two key pillars of the welfare state) during the COVID-19 pandemic and assess whether there is a need for further interventions with regard to the social security and prosperity of citizens.